O equilíbrio econômico-financeiro nas concessões regidas pela Lei nº 8.987/95 - Marolla, Eugenia Cristina Cleto (2010)
The use of concessions for the provision of public services is a tool that has been widely employed by the Local, State and Federal Governments. Through them the State transfer the provision of a public service to a third party, which will perform it at its own risk and being paid for such services. Therefore, the concession encompasses two conflicting interests: on one side the State interests for a suitable service provision and, on the other side, the private interests in profiting through rendering the service. The balance between both interests results in a economic-financial equation, a tool that can guarantee the relationship maintenance, among the benefits and duties agreed by the parties, and which they view as ideal for the attainment of their interests and which should be kept throughout the whole necessarily-long performance of the contract. Nowadays, the maintenance of economic-financial balance stands out in face of the increasing risks and of the need for heavy fund allocation for making the concession viable, which demands luring investments in an extremely competitive market, which has been increasingly requiring greater guarantees. On the other hand, the problems brought forth by the breakdown of the economic-financial equation are the most frequent and stormy in the daily routine of public services concessions, often leading the parties to lengthy and costly litigations. Thus, the reflection on the principle of economic-financial balance and its adaptation to the present situation is necessary, and mainly after the enactment of Law 8.987/95, about the points that generate more questions and about the importance for the improvement of tools for preventing disputes, such as planning, straightforward well-prepared agreement clauses and the performance of ordinary and extraordinary reviews. This paper aims at portraying that legal security creates a virtuous circle concerning the concession agreements, thus being the maintenance of the economic-financial balance mandatory for the accomplishment of this purpose